Developing of environmental education textbook based on local potencies - Silfia Ilma; Fitri Wijarini (University of Muhammadiyah Malang, 2017)
Environmental education subject aims to form students who have the character to maintain the environment. One effort to achieve the objectives of the Environmental education subject is the local Environmental Education Textbook Based on Local Potencies. This research was aimed to produce textbook of environment-based education subject Environmental education based on local potencies. This research and development using Borg & Gall model (1983). This study uses only five stages of the Borg & Gall model, namely (1) need analysis, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, and (5) main product revision, due to time constraints and cost. The results of the research and development that has been done is a textbook of environmental education based on local potencies that is suitable for use in semester 5 collage level.